The Influence of CAR, FDR, and BOPO - Jamaludin, Jamaludin; Rahmah, Siti Ainur; Zakariya, Moh Asep; Mutaqqin, Moch Zaenal; Alhubufillah, M. Alfi; Setiabudi, Rahmat (Jurnal Ekuisci, 2024)
One metric used to assess how well a business is performing is profitability. An organization's capacity to turn a profit can be used to measure performance. A high profitability level indicates excellent success for the organization. Return On Assets (ROA) is the ratio used to determine the degree of profitability. At the same time, the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operating Expenses and Operating Income (BOPO) ratios are known to have an impact on the degree of profitability. This research aims to examine how CAR, FDR, and BOPO affect profitability. This quantitative study utilizes information gathered from Bank Muamalat Indonesia's quarterly financial reports issued between 2013 and 2021. This study employed multiple linear regression with the e-views Nine program as the research method. According to the research's findings, the degree of profitability is significantly impacted by the FDR and BOPO variables but not by the CAR variable. Furthermore, the study's findings indicate that the CAR, FDR, and BOPO variables significantly affect the profitability level simultaneously. The findings of the coefficient of determination (R2) analysis, which indicate that CAR, FDR, and BOPO have an impact on the profitability level, which is 98.60% and 1.40% with the influence of other factors from outside the analysis model, support this.